2016
DOI: 10.1371/journal.pone.0168065
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise on Statin-Associated Skeletal Muscle Myopathy

Abstract: HMG-CoA reductase inhibitors (statins) are the most effective pharmacological means of reducing cardiovascular disease risk. The most common side effect of statin use is skeletal muscle myopathy, which may be exacerbated by exercise. Hypercholesterolemia and training status are factors that are rarely considered in the progression of myopathy. The purpose of this study was to determine the extent to which acute and chronic exercise can influence statin-induced myopathy in hypercholesterolemic (ApoE-/-) mice. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
3
16
2
Order By: Relevance
“…We found that atorvastatin induced an elevation in serum CK level and fatigue index and reduced maximal forelimb strength ( Figure 1 ). These results are consistent with previous findings which indicate that two weeks of statin treatment impairs skeletal muscle function, including reduced grip strength, maximal force, and fatigue [ 37 , 38 ]. In addition, we found that the skeletal muscles of rats treated with atorvastatin had a decreased muscle fiber cross-sectional area and an increased endomysium space ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found that atorvastatin induced an elevation in serum CK level and fatigue index and reduced maximal forelimb strength ( Figure 1 ). These results are consistent with previous findings which indicate that two weeks of statin treatment impairs skeletal muscle function, including reduced grip strength, maximal force, and fatigue [ 37 , 38 ]. In addition, we found that the skeletal muscles of rats treated with atorvastatin had a decreased muscle fiber cross-sectional area and an increased endomysium space ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the last day of the experimental period, all animals were subjected to a grip strength test, as previously described (Chung et al, ). Briefly, mice were held up to the horizontal grip of a dynamometer and pulled steadily backwards until the researcher's strength matched the animal's maximum strength and they could not hold on any longer.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise is recommended for those at risk of cardiovascular disease (i.e., those who take statins). However, there are reports that exercise reveals or exacerbates statin myalgia 13, 14 and myositis 12, 15, 16, and that statins limit training adaptations in skeletal muscle 57, 58. Therefore, we gave statin-treated and control rats access to an in-cage running wheel, which resulted in a type of voluntary exercise similar to that recommended for human subjects prescribed statins.…”
Section: Resultsmentioning
confidence: 99%